FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEPATAN ANAK USIA SEKOLAH DI KABUPATEN PURWAKARTA - Haryanto, Irwan; Lisnawati, Naintina (Sekolah Tinggi Ilmu Kesehatan Holistik, 2017)
Background: Physical fitness levels of students can maximize their mind and energy for school activities. Running speed is part of physical fitness. Nutrition is one of the biological factors that influence in supporting fitness .. Adequacy of nutrients, especially macro nutrients as a source of energy and micro nutrients is closely related to the pattern of consumption. To maintain nutritional adequacy, nutritional structuring needs to be done, including the improvement of nutritional status, maintenance of nutritional status, nutrition matching and recovery of nutritional status. Objective: Analyzing factors related to the speed of running students of class VII junior high school. Method: The type of this research is cross sectional research with purposive sampling technique. The number of samples is 42 students of class VII junior high school 5 Purwakarta. Data analysis was performed by Rank-spearman test technique. Result: There is a significant relationship between energy sufficiency level, protein adequacy level and carbohydrate adequacy level with running speed with p value <0,05. There was no significant relationship between fat sufficiency level, intake of Fe, calcium intake, potassium intake, sodium intake, intake of Zink and magnesium intake with runway rate with p> 0,05 . Conclusion: The level of energy adequacy, the level of protein adequacy and the level of carbohydrate adequacy associated with running speed. The level of fat sufficiency, intake of Fe, calcium intake, potassium intake, sodium intake, intake Zink and magnesium intake not related to the level of running speed.